The Spirit of Fluxus as a Nomadic Art Movement - Wilmer, S.E. (Nordic Theatre Studies, 2014)
Fluxus was the brain-child of a Lithuanian-born artist named George Maciunas whose family fled to Germany in the Second World War, where they eventually became displaced persons and later emigrated to the USA. Maciunas studied art and architecture in Pittsburgh and New York before working as an architect and graphic artist and founded the Fluxus movement at the beginning of the 1960s. During his student years, he became fascinated by nomadic art in Asia and Eastern Europe that would later influence his life’s work. This essay considers the relationship between his interest in nomadism and the nature of the Fluxus movement that spread across the world, breaking down barriers between art and life, privileging concrete and conceptual art, and staging unusual events. It applies Braidotti’s notion of the nomadic subject to Maciunas’ encouragement of radical styles of performance art, such as Yoko Ono’s minimalist conceptual work and Joseph Beuys’s Tatar-influenced use of fat and felt.